2017
DOI: 10.1161/atvbaha.117.310062
|View full text |Cite
|
Sign up to set email alerts
|

Refrigeration-Induced Binding of von Willebrand Factor Facilitates Fast Clearance of Refrigerated Platelets

Abstract: Objective Apheresis platelets for transfusion treatment are currently stored at room temperature because after refrigeration platelets are rapidly cleared upon transfusion. In this study, the role of von Willebrand factor (VWF) in the clearance of refrigerated platelets is addressed. Approach and Results Human and murine platelets were refrigerated in gas-permeable bags at 4°C for 24 hours. VWF binding, platelet signaling events, and platelet post-transfusion recovery and survival were measured. After refrig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 41 publications
1
38
0
Order By: Relevance
“…S5). This conclusion is also supported by previous studies that VWF binding to platelets was induced during cold storage and that refrigeration-induced binding of VWF to platelets facilitates their rapid clearance by inducing GPIbα-mediated signaling 20,33,34 . GPIb-IX complex is a sensor for shear stress-induced platelet activation 35 .…”
Section: Discussionsupporting
confidence: 85%
“…S5). This conclusion is also supported by previous studies that VWF binding to platelets was induced during cold storage and that refrigeration-induced binding of VWF to platelets facilitates their rapid clearance by inducing GPIbα-mediated signaling 20,33,34 . GPIb-IX complex is a sensor for shear stress-induced platelet activation 35 .…”
Section: Discussionsupporting
confidence: 85%
“…The authors demonstrated that the inhibition of this binding and the consequent downstream cascade, using a specific peptide that recognizes GPIb-α, significantly increased recovery and life-span of cold-stored PLTs. 28 Another study showed that a specific caspase-3 inhibitor significantly improves PLT functionality and viability during seven days of storage. 29 This, together with our results, suggests that inhibition of apoptosis seems to be a promising approach to reduce cold-stored lesions.…”
Section: Discussionmentioning
confidence: 99%
“…43,97 Because murine GPIba does not have N-glycosylation sequence motifs, it could not be involved in direct binding with the AMR. 50 Instead, because refrigeration induces binding of plasma VWF to GPIba on the platelet, 43,100 treatment of OGE could conceivably preclude the VWF-GPIba interaction and subsequent clustering of GPIba in refrigerated platelets ( Figure 6C). Consistent with the aforementioned trigger model, shear treatment of refrigerated WT platelets, but not VWF 2/2 ones, results in MSD unfolding, platelet desialylation, and PS exposure.…”
Section: Platelet Storage By Refrigerationmentioning
confidence: 99%
“…Consistent with the aforementioned trigger model, shear treatment of refrigerated WT platelets, but not VWF 2/2 ones, results in MSD unfolding, platelet desialylation, and PS exposure. 100 Furthermore, refrigerated VWF 2/2 platelets, or refrigerated WT platelets incubated with a peptide that inhibits GPIba interaction with VWF, exhibit markedly higher posttransfusion recovery than WT. 100 Thus, it appears that VWF binding, GPIba clustering, platelet desialylation, and PS exposure are key steps to the fast clearance of refrigerated platelets.…”
Section: Platelet Storage By Refrigerationmentioning
confidence: 99%